Contexts and conditions of outgroup influence - Gaffney Amber M.; Souter Stephanie S.; Jung Jiin; Crano William D. (Psychology of Language and Communication, 2023)
The current study examined how the composition of intergroup contexts affects intergroup communication. We propose that when multiple outgroups exist, an extreme faction can make more moderate factions appear reasonable, creating pathways for influence. We also considered the role that an influence target’s fit with their ingroup (self-prototypicality) plays in responses to outgroup influence attempts. Specifically, we propose, and the current study showed, that both the composition of intergroup context and one’s relationship with their own group can create a pathway toward convergence of opinions and willingness to accept an outgroup’s opinion position. Two experiments (American partisans, N = 249), suggest that self-prototypicality in one’s political party positively predicts agreement with an opposing party’s message when the message appears in the presence of a more extreme outgroup than the moderate outgroup alone. This study stresses the importance of considering intragroup and intergroup comparative processes for intergroup communication research.